Pengaruh Suhu Lingkungan Terhadap Inisiasi Terbang Parasitoid Telur Trichogrammatoidea cojuangcoi Nagaraja (Hymenoptera: Trichogrammatldae) - Salblah, Desita (PEST Tropical Journal, 2003)
The objective this research is to obtain information about the effect of environmenttemperature toward flight inisiation egg parasitoid. The experiment use tool likePrasad ef a/. (1999) method wich a PVC cylinder with measurement of high cylinderis 30 cm and diameter cylinder is 7,5 cm. This experiment arranged in a randomizedcomplete design with three environment temperature (13, 18 & 28 Â°C ). Flightinisiation consist of short flight (8-10 cm) and far flight (20-30 cm). The results showedsum of adult flight inisiation of short flight reduce at increase temperature but sumof adult flight inisiation of far increase at increase temperature